Upaya Meningkatkan Kemampuan Menyelesaikan Masalah Matematika Melalui Guided Discovery Learning Menggunakan Microsoft Teams Berbantuan Excel - Aulia Diraswati Septyanggraeni (Postulat : Jurnal Inovasi Pendidikan Matematika, 2020)
COVID-19 pandemic in Indonesia has an impact on learning process, which requires students to learn bynetwork/long distance. One of the platforms that teachers can used is Microsoft Teams. To be able to improvethe ability of students in solving problems in mathematics learning, teachers must make learning situationswith more problems solving, so students can more active in solving problems related to this material. Thelearning model that teachers can use is Guided Discovery Learning. Based on the findings in class, one of themathematics topics in SMK that are still difficult for students to understand is matrix. This is because matrixis considered an abstract material and is not related to everyday life. Students bored in studying matrixbecause this material consists of many numbers and requires high accuracy. So it takes learning media thatcan attract and help students in learning these materials. One of the learning media that can be applied isExcel Matrix. This research was conducted on 34 students of XI APAT 2 in SMK Negeri 1 Grati. Thisresearch is a classroom action research (PTK) which consists of 3 cycles. The results showed that in cycles 1and 2 it was still said to be not good, meaning that students were not yet able to understand problems, plansolutions, carry out solutions, and re-check solutions, while in cycle 3, the ability to solve mathematicalproblems of students could be said to be good according to the success criteria. which is determined as many as 23 students from the total (68%) in good or very good criteria in solving problems.